Sister Mary Joseph’s nodule from primary endometrial carcinoma: a case report - Ramanathan, Annamalai; Nagandla, Kavitha; Jamli, Faiz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Sister Mary Joseph’s nodule (SMJN) refers to umbilical metastases is rare and is likely be the first manifestation of an underlying malignancy likely gastrointestinal or genital in origin. The incidence reported is about 1-3% and has a poor prognosis with an overall survival (OS) of 2-11 months from the initial diagnosis. The ovarian location is incriminated the most common site followed by endometrium in gynaecological cancers. Only 32 cases of SMJN from endometrium with have been reported in the published literature. A 57-year-old postmenopausal woman, presented with a large bleeding and infected umbilical mass and symptomatic anaemia. A diagnosis of SMJN was made following biopsy of the mass which revealed metastasis of an endometrial adenocarcinoma. She underwent 6 cycles of neoadjuvant chemotherapy. Subsequent laparotomy including full resection of the umbilical lesion, abdominal wall reconstruction with composite mesh, and a total abdominal hysterectomy with bilateral salpingo-oophorectomy, omentectomy and bilateral lymph nodes excision. Histological diagnosis revealed metastasis from primary endometrial carcinoma. Currently patient condition is stable and is on follow up. This is the 33rd case as reported in the literature of SMJN originating from endometrial carcinoma from authors knowledge. Our approach was multimodal with neoadjuvant chemotherapy followed by surgery and adjuvant radiotherapy. Currently there is no specific recommendation and management should be individualised.